Finishing properties of polyurethane and acid catalyst based coating on bamboo stripped board / Norain Mokhtar - Mokhtar, Norain (2012)
Finishing process is the last of a sequence of manufacturing actions. The application of finishes is to protect the surface and also enhance the aesthetic value of bamboo strips board. Finishing also helps to enhance the attractiveness of the surface texture, dimensional stability and durability. In this study, bamboo strips board was used as a panel commercial. It uses to substitute the shortage of the other plywood but no information about the finishing on bamboo strips board. So, this study is carried out the suitability of two types of finishing material such as polyurethane and acid catalyst lacquer. From this study, Polyurethane lacquer shows good resistance against gloss and hardness but slightly poor for impact, crosscut and household. Acid catalyst lacquer shows good performance on impact, crosscut and household but slightly poor for hardness and gloss.